1998
DOI: 10.1056/nejm199811053391901
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission after Treatment of Acute Promyelocytic Leukemia with Arsenic Trioxide

Abstract: Low doses of arsenic trioxide can induce complete remissions in patients with APL who have relapsed. The clinical response is associated with incomplete cytodifferentiation and the induction of apoptosis with caspase activation in leukemic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
762
1
8

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,108 publications
(790 citation statements)
references
References 35 publications
19
762
1
8
Order By: Relevance
“…In the US, the Environmental Protection Agency has amended the maximum contaminant level, lowering the standard for arsenic in drinking water from 50 to 10 ppb. Interestingly, arsenic trioxide is a good remedy for treating acute promyelocytic leukemia [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the US, the Environmental Protection Agency has amended the maximum contaminant level, lowering the standard for arsenic in drinking water from 50 to 10 ppb. Interestingly, arsenic trioxide is a good remedy for treating acute promyelocytic leukemia [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…But previous studies indicated that alteration of cell proliferation contributes to its carcinogenicity [5]. On the other hand, arsenic has been used to treat cancers and it brings complete remission of acute promyeloid leukemia [6] . This could be due to the induction of differentiation at lower dose or induction of apoptosis or autophagic cell death at higher dose [7].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic trioxide (As 2 O 3 ) was recently demonstrated to be an effective inducer of apoptosis in patients with relapsed acute promyelocytic leukemia (APL) and in patients with APL in whom all-trans-retinoic acid (ATRA) and conventional chemotherapy has failed. [1][2][3][4] Studies in vitro indicate that As 2 O 3 can induce apoptosis in myeloma cell lines, in plasma cells from myeloma patients, 5 in malignant lymphocytic cell lines 6,7 as well as primary cultures of lymphocytic leukemia and lymphoma cells, 6 in myeloid and B-cell leukemia cell lines, 8 in megakaryocytic leukemia cell lines, 9 in neuroblastoma cell lines 10 and in HPV16-immortalized human cervical epithelial cells. 11 The mechanism responsible for the induction of apoptosis has not been fully characterized, but As 2 O 3 induced apoptosis in NB4 cells, cloned from a relapsed patient with APL, by inducing loss of PML/RARā£ protein 12 and by suppressing expression of the Bcl-2 protein.…”
mentioning
confidence: 99%